Model polydimethylsiloxanes subjected to thermal weathering: Effect on molecular weight distributions - Valles, Enrique Marcelo (2000)
We have subjected samples of model polydimethylsiloxanes of narrow molecular weight distribution to thermo-oxidation in an air circulating oven. Samples remained for up to 1760 h at 200 °C under a standard atmosphere. Loss of average molecular weight and broadening of molecular weight distributions was observed. We have modeled the process assuming that both crosslinking and scission are present simultaneously. We have tried to interpret the experimental data in two different ways: either assuming that the ratio of crosslinking to scission was not constant, or that there is an induction period with no reaction before the polymer shows measurable effects of the attack. We discuss the relative merits of both interpretations.